TAZ Expression on Endothelial Cells Is Closely Related to Blood Vascular Density and VEGFR2 Expression in Astrocytomas. Issue 2 (4th January 2019) - Xu, Chenyue; Mao, Luning; Xiong, Ji; Wen, Jianbo; Wang, Yin; Geng, Daoying; Liu, Ying
Abstract: Significant angiogenesis is one of the malignant features in astrocytomas. Cotransfactor Yes-associated protein/transcriptional coactivator with PDZ-binding motif (YAP/TAZ) is a major regulator of embryonic angiogenesis, in which it plays an essential role in vascular tip cell migration, blood vessel formation, and vascular barrier maturation. We quantified TAZ expression on blood vessels and parenchyma of astrocytomas of varying malignancy to investigate its role in tumor angiogenesis. Replicating others' findings, we observed that TAZ is expressed in tumor cells but also in vascular cells. TAZ expression in both cell types was correlated with malignant grade. Immunofluorescence staining for TAZ, smooth muscle actin, and CD31 verified that TAZ-expressing vascular cells are endothelial cells, not pericytes. Analysis of blood vessel density using CD31 immunolabeling revealed that endothelial cell TAZ immunoreactivity was positively correlated with blood vessel density. MRI-acquired tumor blood perfusion measurements in 12 pre-excision glioblastomas and subsequent postexcision TAZ staining supported that TAZ immunoreactivity-blood vessel density correlation with blood perfusion. In glioblastoma, TAZ staining was denser in glomerular neovascularization than that in the thin-walled neovascularization. TAZ expression was also correlated with vascular endothelial growth factor 2 (VEGFR2) immunoreactivity on endothelial cells. Our results indicate that VEGFR2/TAZ signaling pathway plays an important role in angiogenesis in astrocytomas.